2020
DOI: 10.1371/journal.pone.0230958
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression analysis of miRNAs and elucidation of their role in salt tolerance in rice varieties susceptible and tolerant to salinity

Abstract: Soil salinization is a serious problem for cultivation of rice, as among cereals rice is the most salt sensitive crop, and more than 40% of the total agricultural land amounting to approximately 80 million ha the world over is salt affected. Salinity affects a plant in a varieties of ways, including ion toxicity, osmotic stress and oxidative damage. Since miRNAs occupy the top place in biochemical events determining a trait, understanding their role in salt tolerance is highly desirable, which may allow introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 86 publications
0
26
0
Order By: Relevance
“…Salinity stress is one of the major limiting factors for plant growth and crop productivity, which garners increasing attention in that soil salinization becomes more and more serious worldwide owing to various natural and human activities. , Around the world, approximately 40% of the total agricultural lands are affected by soil salinization . High salinity causes severe damages to plant cells due to the detrimental osmotic, ionic, and secondary stresses by interfering with the ion balance of cells, inhibiting photosynthesis, and destroying the membrane system, protein synthesis, and metabolism pathways. , As known, the plasma membrane (PM) of a plant cell is the most sensitive to salinity. , Under salt stress, amounts of reactive oxygen species (ROS) are accumulated in the cell to attack the unsaturated fatty acids in the PM and disintegrate the membrane system, consequently resulting in plant death. , …”
Section: Introductionmentioning
confidence: 99%
“…Salinity stress is one of the major limiting factors for plant growth and crop productivity, which garners increasing attention in that soil salinization becomes more and more serious worldwide owing to various natural and human activities. , Around the world, approximately 40% of the total agricultural lands are affected by soil salinization . High salinity causes severe damages to plant cells due to the detrimental osmotic, ionic, and secondary stresses by interfering with the ion balance of cells, inhibiting photosynthesis, and destroying the membrane system, protein synthesis, and metabolism pathways. , As known, the plasma membrane (PM) of a plant cell is the most sensitive to salinity. , Under salt stress, amounts of reactive oxygen species (ROS) are accumulated in the cell to attack the unsaturated fatty acids in the PM and disintegrate the membrane system, consequently resulting in plant death. , …”
Section: Introductionmentioning
confidence: 99%
“…In plants, miRNAs regulate proper tissue differentiation, organ and the vascular system development [ 16 ]. The increased expression of miRNA data was also demonstrated in plants subjected to various stress factors, such as drought [ 17 ], salinity [ 18 ], heat [ 19 ], nutrient deficiency [ 20 ], or heavy metals [ 21 ], which indicate that miRNAs are also involved in the adaptation mechanisms to stressful conditions [ 22 ]. When it comes to hypoxia, studies concerning identification of miRNAs were conducted in Arabidopsis thaliana [ 23 ], Zea mays [ 24 ], Populus tomentosa [ 25 ], Medicago sativa [ 26 ], Solanum habrochaites [ 27 ] and Cucumis sativus in the context of adventitious roots formation [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the chilling environment, sRNA mediates hypermethylation of the dormancy-related gene DAM and initiates dormancy ( Zhu et al, 2020a ). Meanwhile, Osa-miR12477 regulates the expression of gene LAO to tolerate salt and reduces oxidative damage ( Parmar et al, 2020 ). It has been reported that RdDM occurs in plants in response to abiotic stress environments, e.g., drought and salinization and biological stresses ( Erdmann and Picard, 2020 ; Liu and He, 2020 ; Kumar and Mohapatra, 2021 ; Table 1 ).…”
Section: Srna Functionsmentioning
confidence: 99%